Comparison of Lipid Profile in Patients With and Without Acute Myocardial Infarction - Mal, Kheraj (Cureus, 2019)
Introduction There is ample data available to determine the impact of deranged lipid values of acute myocardial infarction (AMI); however, there is a paucity of data from low-income countries like Pakistan. In this study, we aim to determine the correlation of lipid values with AMI. Materials and methods This case-control study was conducted from 1 February 2019 to 30 October 2019 in a tertiary care hospital in Sukkur, Pakistan. There were a total of 421 participants divided into two groups; Case Group (patients with AMI, n=212) and Control Group (patients without AMI, n=209). Results Total cholesterol and low-density lipoprotein (LDL) were significantly higher in patients with AMI and HDL was lower. There was no significant difference between triglycerides in both groups. Conclusion Dyslipidemia is an important risk factor for AMI. There is a need for more large scale multi-center studies to further understand the role of lipid profile in AMI and the various factors that influence it.